2006
DOI: 10.1021/jp060492n
|View full text |Cite
|
Sign up to set email alerts
|

Angle-Dependent Terahertz Time-Domain Spectroscopy of Amino Acid Single Crystals

Abstract: The measurement of absorption spectra using angle-dependent terahertz (THz) time-domain spectroscopy for amino acid single crystals of l-cysteine and l-histidine is reported for the first time. Linearly polarized THz radiation enables us to observe angle-dependent far-infrared absorption spectra of amino acid single crystals and determine the direction of the oscillating dipole of the molecules in the 20-100 cm(-1) range. By comparing the THz spectra of a single crystal and powder, we found that there was a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 27 publications
4
61
0
Order By: Relevance
“…We found that the observed THz absorption band resolves into narrower peaks as the temperature is decreased and some of these shift towards higher frequencies. 14,27 Since the behavior of each band is different because of the different nature of the THz absorption, inter-and intramolecular modes can be roughly distinguished by analyzing the temperature-induced shifts of the peaks. For example, the average hydrogen bond strength may decrease with increasing temperature and cause a redshift of the hydrogen bond stretching frequency in the THz region 27 whereas the shifts in the frequency of the intramolecular modes including torsion and a deformation skeleton are rather small with changing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the observed THz absorption band resolves into narrower peaks as the temperature is decreased and some of these shift towards higher frequencies. 14,27 Since the behavior of each band is different because of the different nature of the THz absorption, inter-and intramolecular modes can be roughly distinguished by analyzing the temperature-induced shifts of the peaks. For example, the average hydrogen bond strength may decrease with increasing temperature and cause a redshift of the hydrogen bond stretching frequency in the THz region 27 whereas the shifts in the frequency of the intramolecular modes including torsion and a deformation skeleton are rather small with changing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The optical set-ups and experimental conditions are described elsewhere. 13 Since heat induced frequency shifts and resonance broadening are generally observed for THz peaks, 10,11,14 we measured the THz-TD spectra at room temperature (298 K), 230, 170 and 90 K to observe the spectral properties in detail. The aromatic carboxylic acids incorporated in SBA-16 were packed in the cavity of a plastic cell.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the calculations have not agreed sufficiently well with experimental results, even with small molecules, because the theoretical models do not take complete account of the appropriate crystalline conditions or hydrogen bonding effects. 32 THz-TDS employs several types of optical arrangement classified as transmission, reflection, ATR, and polarization arrangements including ellipsometry. The principles have been detailed elsewhere 23 and here we provide example applications of these methods.…”
Section: Terahertz Time-domain Spectroscopy (Thz-tds)mentioning
confidence: 99%
“…The photon energy of THz radiation can give rise to collective atomic motions of compound. These low-frequency vibrational modes are usually associated with motions of hydrogen-bonding networks which play essential roles on stabilization of biomolecules in solid state [1,2], folding of proteins [3] and solvation of proteins [4] and some other biomolecules [5,6,7,8] in aqueous phase.…”
Section: Introductionmentioning
confidence: 99%